'Selfie Elbow'- A Public Health Problem among Mobile Users - Khanal, Laxman; Khan, Gulam Anwer; Pandeya, Anup (Birat Journal of Health Sciences, 2019)
Introduction: While taking a selfie picture, a person is in a position in which the arm is fully extended or sometimes a little bent and maintained until the picture of choice is adjusted in the camera frame. One Person must have a firm grip on phone to hold it and hit click. When the process is repeated for a few photos, it causes repetitive strain injury, resulting in various signs, including pain in the elbow joint, which has now been named 'selfie elbow.' Doctors assume that as many as 25% of cell phone users in Kolkata are suffering from this problem (selfie-elbow).Although a selfie is generally seen as an expression of self to others, the American Psychiatric Association (APA) has officially confirmed that taking 'selfies' is seen as a mental disorder and has been given the term 'selfitis.' Selfie elbow is a condition due to overuse injury caused by extending and twisting one's arm for too many phone selfies. Like tennis elbow or golfer's elbow, an addiction to selfie-taking and clicking too many can cause pain in your primary picture-snapping elbow and may affect the upper limb, elbow, and shoulder muscles – which leads to degradation in function. Joints involved in the process of selfie-taking are the shoulder joint, the elbow joint, and the wrist joint, all of which help the hand attain a perfect frame for the picture. However, most of the strain is referred to the elbow, because the person extends (or sometimes bends) the elbow in an extremely strained position during the selfie. Selfie elbow is more of an abnormal and repetitive loading of muscles around the elbow, leading to microruptures, and resulting in inflammation and pain; this ultimately heals with scarring, but causes recurrent pain. As stated, it is a form of repetitive stress injury, similar to carpal tunnel syndrome (or the compression of the median nerve in the wrist, usually due to overuse of the hand) and tendonitis (which occurs when the tendon becomes inflamed).